Selecting the Right Type of Educational Experience for Your Agritourism Operation - Joy N. Rumble; Kathryn Stofer; Hoda Manafian (EDIS, 2018)
Agritourism has become a way for consumers to experience agriculture and for the industry to increase agricultural awareness. This 4-page document will help guide you toward selecting the right type of educational experience for your agritourism operation. Written by Joy N. Rumble, Kathryn Stofer, and Hoda Manafian* and published by the UF/IFAS Department of Agricultural Education and Communication, May 2018. https://edis.ifas.ufl.edu/wc304